Clinical outcomes of transcatheter aortic valve implantation: from learning curve to proficiency. Issue 2 (16th August 2016) - Lunardi, Mattia; Pesarini, Gabriele; Zivelonghi, Carlo; Piccoli, Anna; Geremia, Giulia; Ariotti, Sara; Rossi, Andrea; Gambaro, Alessia; Gottin, Leonardo; Faggian, Giuseppe; Vassanelli, Corrado; Ribichini, Flavio
Abstract : Objective: The use of transcatheter aortic valve implantation (TAVI) is growing rapidly in countries with a predominantly elderly population, posing a huge challenge to healthcare systems worldwide. The increment of human and economic resource consumption imposes a careful monitoring of clinical outcomes and cost-benefit balance, and this article is aimed at analysing clinical outcomes related to the TAVI learning curve. Methods: Outcomes of 177 consecutive transfemoral TAVI procedures performed in 5 years by a single team were analysed by the Cumulative Sum of failures method (CUSUM) according to the clinical events comprised in the Valve Academic Research Consortium (VARC-2) safety end point and the VARC-2 definition of device success. Margins for events acceptance were extrapolated from landmark trials that tested both balloon or self-expandable percutaneous valves. Results: 30-day and 1-year survival rates were 97.2% and 89.9%, respectively. Achievement of the primary end point (number of cases needed to provide the acceptable margin of the composite end point of any death, stroke, myocardial infarction, life-threatening bleeding, major vascular complications, stage 2–3 acute kidney injury and valve-related dysfunction requiring a repeat procedure) required the performance of 54 cases, while the learning curve to achieve 'device success' identified 32 cases to reach the expected proficiency. In this experience, the baseline clinical risk as assessed by the Society of Thoracic Surgeons (STS) score determined the long-term survival rather than the adverse events related to the learning curve. Conclusions: A relatively large number of cases are required to achieve clinical outcomes comparable to those reported in high-volume centres and controlled trials. According to our national workload standards, this represents more than 2 years of continuous activity.